2007
DOI: 10.1093/toxsci/kfm244
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxicity—The Risk is Real

Abstract: Several papers published over the last year represent significant progress in closing the gap between rodent immunotoxicity data and human risk and indicate that, at least for the developing immune system, the concern raised by rodent data is justified. The studies reviewed here show that suppression of immune responses in rodents is predictive of suppression of immune responses in humans and that there is a relationship between immune suppression following developmental exposure to the toxicants and enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(90 citation statements)
references
References 42 publications
1
86
0
3
Order By: Relevance
“…Long-term exposure to arsenic impairs lymphocyte, monocyte, and macrophage activity and, in general, affects cellular immune responses (innate immunity) in mammals, resulting in immunosuppression (Duker et al, 2005;Lemarie et al, 2006;Sakurai et al, 2006;Selgrade, 2007;Burchiel et al, 2009;Raqib et al, 2009;Qian et al, 2010). Even at low concentrations, arsenic is known to act as an immunosuppressant (Savabieasfahani et al, 1998;Stepnik et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term exposure to arsenic impairs lymphocyte, monocyte, and macrophage activity and, in general, affects cellular immune responses (innate immunity) in mammals, resulting in immunosuppression (Duker et al, 2005;Lemarie et al, 2006;Sakurai et al, 2006;Selgrade, 2007;Burchiel et al, 2009;Raqib et al, 2009;Qian et al, 2010). Even at low concentrations, arsenic is known to act as an immunosuppressant (Savabieasfahani et al, 1998;Stepnik et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Suppression of antigen-specific antibody responses is considered predictive of immunotoxicity and decreased resistance to infection in rodents (Luster et al, 1992(Luster et al, , 1993Selgrade, 1999); such alterations in murine immune function can be suggestive of health risks in similarly exposed humans (Selgrade, 2007). We previously reported that exposure to !3.75 mg PFOA/kg/day for 15 days suppressed the TDAR in C57BL/6N mice.…”
mentioning
confidence: 99%
“…The percentage of 14 C PCB 77 present/total injected in shell samples varied according to embryonic day and vehicle (Table 1). Table 2 shows the MANOVA for 14 C PCB 77 uptake in a matrix of comparison of the different groups over embryonic day (1,5,10), vehicles (fatty acid and corn oil), and injection sites (air cell and albumen). Significant changes (p < 0.0001) in 14 C PCB 77 concentration confirmed movement of PCB 77 between the egg components over embryonic development, with no difference associated with vehicle type or injection site.…”
Section: Shellmentioning
confidence: 99%